Determinantes de evoluç\~ao da produtividade do trabalho no Brasil: 1990-2009 - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The main goals of this article are the calculus of the productivity per worker in Brazil during 1990-2009 and the identification of its determinants. Firstly, we conclude that the average growth of productivity is 1,05% per year during 1990-2009. Secondly, we identify as most important productivity determinants technological change and exports growth.
Keywords: E23; 330; labour productivity; productivity determinants